2005
DOI: 10.1161/circulationaha.104.504639
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Association of the Angiotensin-Converting Enzyme Insertion/Deletion Polymorphism on Blood Pressure and Cardiovascular Risk in Relation to Antihypertensive Treatment

Abstract: Background-Previous studies have reported that blood pressure response to antihypertensive medications is influenced by genetic variation in the renin-angiotensin-aldosterone system, but no clinical trails have tested whether the ACE insertion/deletion (I/D) polymorphism modifies the association between the type of medication and multiple cardiovascular and renal phenotypes. Methods and Results-We used a double-blind, active-controlled randomized trial of antihypertensive treatment that included hypertensives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
3
6

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(117 citation statements)
references
References 40 publications
7
101
3
6
Order By: Relevance
“…Subjects with the DD genotype exhibited higher tissue ACE activity and increased ACE expression in the plaque of acute coronary syndrome, observations that may explain why hypertensive patients with the DD genotype have a higher incidence of cardiovascular disease. In contrast, in the GenHAT study, 15 the ACE I/D genotype was not a predictor of CVD, nor did it modify the response to antihypertensive treatment. A major difference between the present cohort study and the GenHAT study is the race of the participants.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Subjects with the DD genotype exhibited higher tissue ACE activity and increased ACE expression in the plaque of acute coronary syndrome, observations that may explain why hypertensive patients with the DD genotype have a higher incidence of cardiovascular disease. In contrast, in the GenHAT study, 15 the ACE I/D genotype was not a predictor of CVD, nor did it modify the response to antihypertensive treatment. A major difference between the present cohort study and the GenHAT study is the race of the participants.…”
Section: Discussionmentioning
confidence: 67%
“…18 Although some studies have reported that administration of ACE-Is and/or ARBs vary the effect of the ACE I/D genotype on cardiovascular events, 25 others have not. 15 Although we only have baseline information about antihypertensive treatments, the ACE DD genotype was an independent risk factor for CVD after adjusting for ACE-I/ARB drugs and antihypertensive drugs. A previous report 26 revealed an association between aldosterone escape and the DD genotype, suggesting an influence by aldosterone escape.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…27 Our findings could contribute to the understanding of the pharmacogenetics of ACErelated drugs. Although no pharmacogenetic association between ACE insertion/deletion genotype and blood pressure response was identified in a large-scale clinical trial study, 28 it is shown by us in people with a relatively high number of ACE-activity-raising alleles/genotypes, those who take the ACEI show a lower mean blood pressure values than those who do not. Conversely, in people having no such alleles, disadvantageously higher mean blood pressure values are observed in those taking ACEI than those not.…”
Section: Discussionmentioning
confidence: 71%